Kajian Termal Permukiman Pesisir Perairan Laut dan Perairan Darat - Armiwaty Armiwaty; Umara Hasmarani Rizqiyah; Husnirrahman J; Muhammad Haristo Rahman; Andi Ahmad Fauzan Bachtiar (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study aims to analyze the differences in thermal conditions between coastal and riverside settlements, focusing on variations in temperature, humidity, and wind speed during day and night. The research sites include the coastal area of Dusun Karama Tengah (seaside) and Desa Salotengnga (riverside). Measurements indicate that the coastal area experiences more extreme daytime temperature fluctuations, reaching nearly 39 °C, with nighttime temperatures remaining warm and showing noticeable variation among points. In contrast, the riverside area displays more stable temperature patterns, with nighttime temperatures ranging between 28–30 °C. Relative humidity along the coast increases consistently at night, whereas in the riverside area it is heterogeneous, varying from saturated to very dry conditions. Wind speed serves as a key differentiating factor: the coastal area is still influenced by land–sea breezes, while the riverside environment tends to be stagnant with weak natural ventilation. These findings highlight distinct thermal comfort challenges in both settings—coastal areas are prone to daytime heat stress, whereas riverside areas face nighttime discomfort due to humidity and air stagnation. The results provide a foundation for adaptive architectural and spatial design strategies responsive to local microclimatic contexts.